Decentralization, corruption, and political accountability in developing countries (2007)
Powerful local elites are quite common in developing countries. Thus, whether decentralization reduces or not the level of corruption in the presence of these elites is a relevant issue for these economies. We motivate this paper with some empirical evidence. Using cross-country information we find that the negative average effect of decentralization on corruption documented in the literature is absent for developing countries. Then, we build an imperfect information model of corruption and political accountability to study if the influence local elites may have on the allocation of public resources can explain this outcome. We find that not only the power of the elites but also other unexpected factors matter. In particular, both the existence of regions with a relatively weak accountability sector and the design of decentralization and grants can also explain the lack of success of decentralization in combating corruption in these economies.